2019
DOI: 10.1080/09540105.2018.1547687
|View full text |Cite
|
Sign up to set email alerts
|

Naturally oxidized olive oil exacerbates contact hypersensitivity by promoting differentiation into effector T cells and increasing antigen-specific IFN-γ production

Abstract: The roles of differentiation and cytokine production of helper T and killer T cells by antigen stimulation were investigated to clarify the mechanisms of CHS exacerbation by naturally oxidized olive oil. Mice were orally administered naturally oxidized olive oil once every 2 days for 1 week after sensitization. IL-18 expression in the ear auricle and AP-1 and caspase-1 activity in the splenocytes were measured. The splenic T cell subpopulation and IL-4 and IFN-γ production in each subpopulation were also analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…We previously demonstrated that the consumption of oxidized olive oil exacerbates contact hypersensitivity, a delayedtype allergy, and that this exacerbation was caused by the increased production of IL-18 during the sensitization phase, resulting in the increased production of IFN-γ and Th1. 22,23) In this study, administration of an ingestible amount of oxidized olive oil increased Th2 immunity and exacerbated the immediate allergic reaction. Oxidized olive oil increased serum IgE levels and mRNA expression of Th2 cytokines in regional lymph nodes, and exacerbated ACA.…”
Section: Discussionmentioning
confidence: 52%
“…We previously demonstrated that the consumption of oxidized olive oil exacerbates contact hypersensitivity, a delayedtype allergy, and that this exacerbation was caused by the increased production of IL-18 during the sensitization phase, resulting in the increased production of IFN-γ and Th1. 22,23) In this study, administration of an ingestible amount of oxidized olive oil increased Th2 immunity and exacerbated the immediate allergic reaction. Oxidized olive oil increased serum IgE levels and mRNA expression of Th2 cytokines in regional lymph nodes, and exacerbated ACA.…”
Section: Discussionmentioning
confidence: 52%